Tracing the architecture of caffeic acid phenethyl ester cocrystals: studies on crystal structure, solubility, and bioavailability implications - Ketkar, Sameer; Pagire, Sudhir K.; Goud, N. Rajesh; Mahadik, Kakasaheb R.; Nangia, Ashwini; Paradkar, Anant (Crystal Growth & Design, 2016)
Caffeic acid phenethyl ester (CAPE) is a polyphenolic active compound present in popular apiproduct, "propolis", obtained from beehives, Though it has broad therapeutic capability, the bioavailability of CAPE is limited due to poor solubility. In this study, we report novel cocrystals of CAPE engineered using coformers such as caffeine (CAP), isonicotinamide (INIC), and nicotinamide (NIC) with enhanced solubility and bioavailability of CAPE. The cocrystals were prepared by microwave-assisted cocrystallization and characterized using PXRD, DSC, and Raman spectroscopy. PXRD and DSC confirm the successful formation and phase purity of CAPE-CAF, CAPE-INIC, and CAPE-NIC cocrystals. Raman spectra of CAPE cocrystals complement these results in confirming the formation of novel crystalline phases. CAPE-NIC cocrystal was further subjected X-ray crystallography to understand its molecular arrangement and hydrogen bonding in the crystal structure. The CAPE-NIC cocrystal structure is found to be stabilized by a rare 1,2-benzenediol-amide heterosynthon. Cocrystallization of CAPE with NIC improved its aqueous solubility and pharmacokinetic profile, thereby demonstrating a 2.76-fold escalation in bioavailability.